THE INFLUENCE OF OWNERSHIP STRUCTURE TO FIRM’S PERFORMANCE OF PROPERTY AND REAL ESTATE SECTOR LISTED ON INDONESIA STOCK EXCHANGE (IDX) IN THE YEAR OF 2010–2013 - B12111010, ELLEN OCTAVIANI (Jurnal Manajemen Update, 2015)
This research was conducted to analyze the relationship between the ownership structure and the firm’s performance of property and real estate sector listed on Indonesia Stock Exchange (IDX) during the year of 2010 to 2013.The ownership structure is represented by the institutional and managerial ownership, while Economic Value Added (EVA) as Model I and Tobin’s Q (Q ratio) as Model II are used as a proxy for the firm’s performance. The sampling technique used in this research is purposive sampling and 13 companies were selected as the research sample. Multiple regression model and Panel Data technique have been employed to foresee the relationship among the variables. Model I result showed that the institutional ownership has significant negative effect on EVA, the managerial ownership has partially significant negative effect on EVA, and the company’s size has significant positive effect on EVA. Model II result showed that individually the institutional ownership, the managerial ownership, and the company’s size have the positive, but not significant effect on Tobin’s Q.   Keywords: institutional ownership, managerial ownership, the company’s size, economic value added (EVA), tobin’s Q